2019
DOI: 10.3390/coatings9010060
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Nitrogen/Silicon Doped Vertically Oriented Graphene Produced by ICP CVD Roll-to-Roll Technology

Abstract: Simultaneous mass production of high quality vertically oriented graphene nanostructures and doping them by using an inductively coupled plasma chemical vapor deposition (ICP CVD) is a technological problem because little is understood about their growth mechanism over enlarged surfaces. We introduce a new method that combines the ICP CVD with roll-to-roll technology to enable the in-situ preparation of vertically oriented graphene by using propane as a precursor gas and nitrogen or silicon as dopants. This ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 96 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…The crystalline structure of ibuprofen-Fe 3 O 4 -GO nanospheres was examined by X-ray powder diffraction in comparison with patterns of pristine ibuprofen (Table S5), GO and Fe 3 O 4 -GO nanoplatform (Figure c and Table ). The XRD pattern of GO in a solvent-free state shows two distinct reflexes at 2θ = 11.73° and 24.53° with the interplanar spacing values ∼8.759 and ∼4.215 Å, which can be assigned to (001) and (003) of GO . The interplanar spacing of the (001) plane is 0.779 Å higher than in graphite intercalation compound (∼7.980 Å) during the process of GO formation, which is indicative of the intercalation of oxygen atoms in the forming oxidized domains.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystalline structure of ibuprofen-Fe 3 O 4 -GO nanospheres was examined by X-ray powder diffraction in comparison with patterns of pristine ibuprofen (Table S5), GO and Fe 3 O 4 -GO nanoplatform (Figure c and Table ). The XRD pattern of GO in a solvent-free state shows two distinct reflexes at 2θ = 11.73° and 24.53° with the interplanar spacing values ∼8.759 and ∼4.215 Å, which can be assigned to (001) and (003) of GO . The interplanar spacing of the (001) plane is 0.779 Å higher than in graphite intercalation compound (∼7.980 Å) during the process of GO formation, which is indicative of the intercalation of oxygen atoms in the forming oxidized domains.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The XRD pattern of GO in a solvent-free state shows two distinct reflexes at 2θ = 11.73°and 24.53°with the interplanar spacing values ∼8.759 and ∼4.215 Å, which can be assigned to (001) and (003) of GO. 64 The interplanar spacing of the (001) plane is 0.779 Å higher than in graphite intercalation compound (∼7.980 Å) during the process of GO formation, which is indicative of the intercalation of oxygen atoms in the forming oxidized domains. On the other hand, the d ∼8.759 Å of (001) is comparable to the lattice expansion of (001) in GO caused by intercalation of 1-propanol (∼8.650 Å).…”
Section: Chemical Bond Formation Between Ibuprofen Fe 3 O 4 and Gomentioning
confidence: 98%
“…Rozel et al succeeded in combining ICP-RF-PECVD with roll-to-roll technology to prepare nitrogen/silicon doped vertically oriented graphene (VOG) by using propane (C 3 H 8 ) as a precursor gas and nitrogen or silane as dopants. They also found that longer deposition time caused carbon amorphisation and increased sp3-hybridized carbon fraction, resulting in expansion of vertically oriented carbonaceous and pillars growth [ 109 ].…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…Nanostructured carbon coatings for steel electrodes, due to their remarkable characteristics, such as high electrical conductivity, hydrophobicity, and chemical inertness, have found a place in many applications as proton-exchange membrane fuel cells [1], porous current collectors for lithium-ion batteries [2], and as an effective support to grow carbon nanotubes [3][4][5], vertically-oriented graphene [6], carbon fibers [5] and micro-sized carbon spheres [5]. However, the coating properties can vary widely due to the substrate composition and synthesis conditions, for example, different qualities of the carbon layer can both support or worsen the substrate corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%